Two anatomically specific classes of candidate cholinoceptive neurons in the rat olfactory bulb - Nickell, WT (J Neurosci, 1988)
The pharmacohistochemical technique of Butcher (1978) and choline acetyltransferase (ChAT) immunocytochemistry were used to demonstrate the presence, morphology, and differential distribution of 2 classes of acetylcholinesterase (AChE)-positive, ChAT-negative neurons in the rat olfactory bulb. One population of these neurons is located preferentially in a stratum just deep to the mitral cell layer (mcl). These AChE-positive intramitral neurons are significantly larger than the predominant inframitral neuronal type, the granule cell. Inframitral AChE-positive neurons appear to send processes deeper into the granule cell layer and superficially into the external plexiform layer (epl), above the mcl. Neurophysiological experiments reported in a companion article are consistent with the existence of a population of cholinoceptive neurons with the location and characteristics of these large inframitral interneurons. A second class of AChE-positive, ChAT-negative neurons is found exclusively in the glomerular layer. These neurons are located primarily in the periglomerular region and the superficial third of the epl; they are somewhat larger than typical periglomerular cells. Juxtaglomerular AChE neurons are smaller than inframitral AChE neurons. Since there are no neurons in the olfactory bulb that produce ChAT, the synthetic enzyme for ACh, the AChE-positive cells reported here are hypothesized to be cholinoceptive neurons for the cholinergic projection from the basal forebrain to the olfactory bulb. Anatomical, physiological, and receptor-ligand binding data are consistent with this interpretation.